POTENSI PENGEMBANGAN RUANG TERBUKA HIJAU (RTH) DI KECAMATAN SEBERANG ULU II KOTA PALEMBANG - Rosianty, Yuli; Fahmi, Innike Abdillah; Lensari, Delfy; Pernandes, Fredi (Universitas Muhammadiyah Palembang, 2019)
Green open space (RTH) is one of the most important elements in urban areas that can function to balance the ecological conditions in an area so that there is a balance between ecosystems and development developments in the modern era. But the pace of urban development often does not consider the existence of green space. Other than that, many people do not know the existence and function of green space, so it often looks like being ignored and not maintained. In this case, researchers are interested in identifying the potential presence of green open space in the Seberang Ulu II sub-district of Palembang. This study will collect data on the location of each green space in the Seberang Ulu II sub-district, identification of existing vegetation types, estimation of carbon storage, and the level of understanding of the Seberang Ulu II community on the existence and function of green space. The method used is to use plot sampling to determine the level of diversity of green space and the distribution of questionnaires to determine the level of community understanding. The results showed that the area of green open space in the Seberang Ulu II sub-district was only 1.88% of the total area. From the open green space location in Seberang Ulu II Subdistrict, there are 33 species of green open vegetation plants. Where Angsana plants (Pterocarpus indicus), trembesi (Albizia saman), palm (Elaeis guineensis Jacq.), Glodogantiang (Polyathea longifolia) and palm (Mascarena sp) become a plant that dominates and has the highest INP value.Ruang terbuka hijau (RTH) merupakan salah satu elemen terpenting di perkotaan yang dapat berfungsi untuk menyeimbangkan keadaan ekologi pada suatu kawasan agar terjadi keseimbangan antara ekosistem dan perkembangan pembangunan di era modern. Tetapi, laju pembangunan perkotaan seringkali tidak mempertimbangkan keberadaan RTH. Selain itu, banyak masyarakat yang tidak mengetahui keberadaan dan fungsi RTH sehingga sering terlihat seperti terabaikan dan tidak terpelihara. Dalam hal ini peneliti tertarik untuk mengidentifikasi potensi keberadaan RTH di Kecamatan Seberang Ulu II Kota Palembang. Penelitian ini akan dilakukan pendataan lokasi luas masing-masing RTH yang ada di Kecamatan Seberang Ulu II, identifikasi jenis vegetasi yang ada, dan estimasi simpanan karbon, serta tingkat pemahaman msyarakat Seberang Ulu II terhadap keberadaan dan fungsi RTH. Metode yang digunakan adalah menggunakan plot sampling untuk mengetahui tingkat keanekaragaman RTH dan penyebaran kuesioner untuk mengetahui tingkat pemahaman masyarakat. Hasil penelitian menunjukkan bahwa luasan RTH di Kecamatan Seberang Ulu II hanya sebesar 1,88% dari luasan wilayahnya. Dari lokasi RTH yang tersebar di Kecamatan Seberang Ulu II terdapat 33 jenis tanaman penyusun vegetasi RTH dimana tanaman angsana (Pterocarpus indicus), trembesi (Albizia saman), sawit (Elaeis guineensis Jacq.), glodogantiang (Polyathea longifolia) dan palem (Mascarena sp) menjadi tanaman yang mendominasi dan memiliki nilai INP tertinggi.